Risk factors associated with outcome in goats with encephalitic listeriosis: A retrospective study of 36 cases from 2008 to 2021 - Shari Kennedy; Thomas Passler; Jenna Stockler; Jenna Bayne (Journal of Veterinary Internal Medicine, 2023)
Abstract Background There exists a scarcity of information on risk factors associated with case outcomes in goats diagnosed with encephalitic listeriosis. Objective Evaluate risk factors associated with outcomes in 36 cases of suspected encephalitic listeriosis in goats presented to a referral hospital. Animals Thirty‐six goats (26 does, 7 bucks, and 3 wethers) were presented to Auburn University Large Animal Teaching Hospital between 2008 and 2021 for treatment of neurologic disease diagnosed as encephalitic listeriosis based on any combination of clinical signs, cerebral spinal fluid (CSF) analysis, or postmortem examination. Methods Retrospective study. Data were analyzed as binary and under a proportional odds model. The medical records were searched for presumptive encephalitic listeriosis in goats between 2008 and 2021. Data collected included signalment (sex, age, and breed), history, clinical signs, temperature, and ability to stand at presentation. Final diagnosis, CSF results, all treatments, outcomes, and results of necropsy were also collected for analysis. Results Male goats were 14 (95% CI: 1.98‐166.0) times more likely to be a non‐survivor compared to females despite being presented with similar history, clinical signs, and treatments. Animals presented with circling or a history of circling were 6.24 (95% CI: 1.40‐23.21) times more likely to be a survivor than a non‐survivor. Other risk factors evaluated were not significantly associated with outcomes. Conclusions and Clinical Importance Few risk factors were associated with outcomes. Duration of clinical signs, antimicrobial or anti‐inflammatory choices, or CSF results were not associated with outcome. Only sex and history or presence of circling were associated with case outcomes.